Spectroscopic investigations of detachment on the MAST Upgrade Super-X divertor. (1st January 2023) - Verhaegh, K.; Lipschultz, B.; Harrison, J.R.; Osborne, N.; Williams, A.C.; Ryan, P.; Allcock, J.; Clark, J.G.; Federici, F.; Kool, B.; Wijkamp, T.; Fil, A.; et al.
Abstract: We present the first analysis of the atomic and molecular processes at play during detachment in the MAST-U Super-X divertor using divertor spectroscopy data. Our analysis indicates detachment in the MAST-U Super-X divertor can be separated into four sequential phases: first, the ionisation region detaches from the target at detachment onset leaving a region of increased molecular densities downstream. The plasma interacts with these molecules, resulting in molecular ions ( D 2 + and/or D 2 − → D + D − ) that further react with the plasma leading to molecular activated recombination and dissociation (MAR and MAD), which results in excited atoms and significant Balmer line emission. Second, the MAR region detaches from the target leaving a sub-eV temperature region downstream. Third, an onset of strong emission from electron–ion recombination (EIR) ensues. Finally, the electron density decays near the target, resulting in the bulk of the electron density moving upstream. The analysis in this paper indicates that plasma–molecule interactions have a larger impact than previously reported and play a critical role in the intensity and interpretation of hydrogen atomic line emission characteristics on MAST-U. Furthermore, we find that the Fulcher band emission profile in the divertor can be used as a proxy for the ionisation region and may also be employed as a plasma temperature diagnostic for improving the separation of hydrogenic emission arising from electron-impact excitation and that from plasma–molecular interactions. We provide evidences for the presence of low electron temperatures (≪0.5 eV) during detachment phases III–IV based on quantitative spectroscopy analysis, a Boltzmann relation of the high- n Balmer line transitions together with an analysis of the brightness of high- n Balmer lines.